Island and Riverine populations of Alouatta belzebul from the Brazilian Amazon parasitized by Pediculus mjobergi - Guimarães, Victor Yunes [UNESP]; de Albuquerque, Ana Cláudia Alexandre [UNESP]; do Vale e Silva, Alexandre Henrique Cardoso; Wilmsen, Maurício Orlando [UNESP]; Lux Hoppe, Estevam G. [UNESP]; Takahira, Regina Kiomi [UNESP] (Elsevier, 2020)
Mammalian lice are obligate hematophagous ectoparasites that remain on the host throughout the life cycle. This study showed an endangered wild howler species (Alouatta belzebul) parasitized by Pediculus mjobergi. Twenty-seven primates were rescued during wildlife rescue activities in the process of vegetation suppression at the Belo Monte Hydroelectric Power Plant (UHE), located on the lower Xingu River, in the Brazilian Amazon basin. Among the 27 primates examined from two vegetal formations (alluvial rainforest and liana-infested forest) areas, 13 (48.15%) were parasitized by lice with all positive primates being from alluvial rainforest. Optical and scanning electron microscopy allowed the visualization of the structures and the diagnostic characters of the lice species in greater detail expanding the current description. These results highlight the importance of considering ecological and regional features to provide a better understanding of the factors that promote parasitism.
Keywords: Amazon basin; Louse infestation; Microscopy; Parasite ecology; Wild howler